The Effect of Changes in Labor Demand and Entrepreneurship on Income Inequality Through Innovation - Sun, Yichen (Journal of Applied Business and Economics, 2022)
The highly skill-biased technological changes brought about by innovation have changed the employment market greatly. This paper examines the impact of changes in labor demand and entrepreneurship, as a result of technological innovation, on income inequality in the form of a literature review, with analysis of related theoretical and empirical research studies. Innovation is positively correlated with income inequality from two points of view – labor demand and entrepreneurship. Firstly, innovations alter the demand for high-skilled and unskilled labor, and thereby change the skill premia– developments which, in turn, influence income inequality. Secondly, increased entrepreneurship enables entrepreneurs to accumulate more wealth due to higher financial returns. The paper departs from the approach adopted in most traditional papers, which analyze the relationship from a single perspective, by taking a multi-angled approach, with examination of the effect of labor demand and entrepreneurship on income equality from innovations. The study also identifies research gaps in the current literature and direction exploring the effects of innovation on income inequality going forward.